Pengaruh Kualitas Pelayanan dan Harga Terhadap Kepuasan PelangganPengguna Jasa Kereta Api Menoreh Kelas Ekonomi Studi Kasus Pada PT. Kereta Api Indonesia DAOP IV Semarang - Kurnia Triantoro; Sudharto Prawata Hadi; Sri Suryoko (Jurnal Ilmu Administrasi Bisnis, 2015)
Competitive conditions of transport can be viewed through the service aspects of the transportation service provider. Provide service to the customer is a distinct advantage for the company. Quality of service in the company is the company's efforts to complete the consumer desires, so consumers judge that the price issued is according to the need of consumers. Percentage Menoreh Economy Class Train in Quarter I to the second quarter decreased by 30%. In the next quarter, namely the seconde quarter to the third quarter of the percentage of passengers increased by 54%. But in the third quarter to the fourth quarter the percentage increase in passengers is smaller than the percentage of 26% the previous quarter, in which each company has a hope to continue increase the number of passengers each period and improve facilities and services for the better. This study aimed to determine the effect of quality of service and price to customer satisfaction Menoreh Train.This study aimed to determine the effect of quality service and price to Menoreh Train customer satisfaction.This type of research is explanatory research. This research was uses 100 respondents who had used the Menoreh Train more than once in last three months. The sampling technique of this research is purposive sampling and accidental sampling, with data collection techniques are interviews, questionnaires, and literature. The method of analysis is validity test, reliability test, crosstab, correlation coefficient, coefficient of determination, simple linear regression, t test, multiple linear regression, and F test.The result of this analysis is variable quality of service has a partial effection of customers satisfaction by 23,5%, variable of price is partially affecting customer satisfaction by 32,1%. The quality of service and price are jointly significant effect on customer satisfaction by 39,6%.Suggestions for PT. Kereta Api Indonesia DAOP IV Semarang is should pay attention and develop the existing facilities in Menoreh Train, and maintains the ticket price of Menoreh Train, if there is a company policy to increase the ticket price of Menoreh Train expected according to the range of passenger purchasing power.